Understanding decision-makers and their needs: framing Global Burden of Animal Diseases offerings to enhance relevance and increase impact - Smith, D.; Cooper, T.L.; Utomo, B.N.; Wiyono, A.; Kusumaningtyas, E.; Endrawati, D.; Adji, R.S.; Tenzin, G.; Nuradji, H.; Dharmayanti, N.L.P.I.; Grace, Delia (World Organisation for Animal Health, 2024)
In a world characterised by data deserts and data swamps, translating evidence into actionable policies and practices is not easy. This article addresses this challenge through the lens of evidence emerging from the Global Burden of Animal Diseases (GBADs) initiative. It emphasises the need for an intentional approach that connects research information with the specific needs of decision-makers and identifies specific impact pathways associated with different groups of decision-makers. The GBADs programme aims to support animal health decisions, and the authors outline the diverse landscape of decision-makers in this field, encompassing the public and private sectors, livestock keepers, civil society and international development agencies. Key issues such as disease prioritisation and lobbying are also discussed. The authors propose an ‘evidence ecosystem’ approach, one that understands data users and their interactions, for analysing the needs of decision-makers, and framing GBADs offerings according to these needs. Two case studies, a recently concluded global case study of disease prioritisation decision-making and an ongoing policy analysis and needs assessment for GBADs in Indonesia, are presented to demonstrate how evidence ecosystem analysis and audience segmentation could be used to tailor GBADs information offerings for different decision-making groups. The article concludes by recommending that GBADs’ future applications prioritise information offerings, adapt them to decision-makers’ needs and consider how different segments of decision-makers will utilise the information to achieve real-world impacts.